Barrages et développement dans les Alpes françaises de l’entre-deux-guerres - Anne Dalmasso (Revue de Géographie Alpine, 2008)
The heated discussions and controversies over large dams that marked the start of the 21st century have led us in this article to examine the conditions under which Alpine dams were received during the first construction phase of the 1920s and 1930s. Although the extent of social and environ-mental impacts was not the same, the types of questions raised concerning methods of appropriation and uses to which water was put are similar. Among the arguments for and against, which always tend to be structured around the promotion or denunciation of the virtues of modernisation and development, the acceptability of dams depends firstly on the disturbances caused to the distribution of property rights and land usage rights and the ability to balance out gains and losses among the different social groups concerned. These questions are examined in the light of two dams constructed in the French Alps in the 1930s, the Chambon and Sautet dams.